Estudo de caso: Moodle e pedagogia da alternância nos cursos de especialização do Pronera em Residência Agrária - Rech, Aline Pereira de Arruda (2015)
The use of information and communication technologies are an innovation in educational practices, one example is the virtual teaching and learning environments (AVEA), Moodle. However for using Moodle AVEA be a facilitator practices in teaching and learning teachers must adapt to this reality with technological fluency. The research sought to investigate the use of Moodle as an aid in pedagogy of alternation in the Specialization Course in Peasant Family Farming and Countryside Education II of the Federal University of Santa Maria - Brazil, and produce video tutorials as a methodological tool to assist in the use of Moodle AVEA Land in residence courses in Brazil included the call of CNPQ / MDA-INCRA No. 26/2012. The survey was conducted with qualitative approach. Initially questionnaires were applied to the subjects. They were also produced videos tutorials for training in the use of Moodle. The conclusion is the need for more training for teachers as an incentive for the use of AVEA and the inclusion of a tutor to support students in the development of activities. The training with the help of the video tutorials, demonstrated effectiveness, as some universities interested in entering information to the AVEA and did so fully using all environment tools.